Description of Anxiety, Stress and Depression Levels in Post Flood Disaster - Azna Yuliana; Subhannur Rahman; Rian Tasalim (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The magnitude of the impact of the floods that have almost paralyzed all activities of the local community, the number of roads that are submerged, the destruction of public facilities and residential areas and the emergence of health problems make people at the disaster site feel deep trauma. This study aims to determine the description of the level of anxiety, stress and depression after the flood disaster in the people of Paku Alam Village, Sungai Tabuk District, Banjar Regency. The design of the study used descriptive. The sample of this study was taken with an accidental sampling technique of 86 people from Paku Alam Village, Sungai Tabuk District, Banjar Regency in 2022. This study used a DASS 21 questionnaire presented in the form of frequency distribution. The results showed that as many as 56 people (65.1%) were normal, as many as 10 people (11.6%) experienced mild anxiety, as many as 19 people (22.1%) experienced moderate anxiety, and as many as 1 person (1.2%) experienced severe anxiety. A total of 76 people (88.4%) were normal, as many as 9 people (10.5%) experienced mild stress, and as many as 1 person (1.2%) experienced severe stress. A total of 73 people (84.9%) were normal, as many as 4 people (4.7%) had mild depression, as many as 8 people (9.3%) had moderate depression and as many as 1 person (1.2%) had severe depression. Most of the respondents experienced normal anxiety, stress and depression about the flood disaster that occurred in Paku Alam Village, Sungai Tabuk District, Banjar Regency.